Uso do potencial evocado auditivo de tronco encefálico automático e monitoramento auditivo na identificação precoce da deficiência auditiva infantil - Nunes, Glaurea Regina de Santana (2023)
Introduction: Neonatal Hearing Screening aims to early identify a possible hearing impairment in newborns and infants, favoring the diagnosis and intervention of hearing impairment in a timely manner. Objective: To investigate the use of automatic brainstem auditory evoked potential in neonatal hearing screening and to emphasize the importance of auditory monitoring in the early identification of hearing loss. Methodology: Article 1 is an ecological, descriptive study of a time series of newborns who underwent the automatic examination of Brainstem Auditory Evoked Potential in neonatal hearing screening, from 2008 to 2020, in all Brazilians states. The number of automatic Brainstem Auditory Evoked Potential tests performed in all Brazilian states, the presence of automatic Brainstem Auditory Evoked Potential equipment in public hospitals and Neonatal Intensive Care Unit beds were analyzed. Article 2 used a case study, which describe the trajectory of a child who underwent Neonatal Hearing Screening with a negative result for hearing loss, but who, in 2000, developed an acquired hearing loss. Results: There was an increase in the number of automated Brainstem Auditory Evoked Potential tests performed in neonatal hearing screening in the analyzed period . The analyzed case demonstrated the lack of surveillance of the child by the multidisciplinary team and the relevance of considering audiological follow-up as an important step. Conclusions: Despite the positive evolution, the performance of the Automatic Brainstem Auditory Evoked Potential test in neonatal hearing screening is far below expectations for the existing demand. The lack of audiological follow-up can lead to a late diagnosis of acquired hearing loss.